2012
DOI: 10.1007/s00216-011-5697-5
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative detection of desmopressin in plasma by liquid chromatography–tandem mass spectrometry

Abstract: This work describes a liquid chromatography-electrospray tandem mass spectrometry (LC-ESI-MS/MS) method for detection of desmopressin in human plasma in the low femtomolar range.Desmopressin is a synthetic analogue of the antidiuretic hormone arginine vasopressin and it might be used by athletes as masking agent in the frame of blood passport controls. Therefore, it was recently added by the World Anti-Doping Agency (WADA) to the list of prohibited substances in sport as a masking agent. Mass spectrometry char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
(21 reference statements)
2
16
0
1
Order By: Relevance
“…b) with good intensities ( m/z 328.0, 120.0, 214.0, 276.1, 430.4 and 526.7). The origin of these fragments has been explained previously (Esposito et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…b) with good intensities ( m/z 328.0, 120.0, 214.0, 276.1, 430.4 and 526.7). The origin of these fragments has been explained previously (Esposito et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The high elimination rate from blood circulation of desmopressin and the low bioavailability of oral and intranasal formulations (Agerso et al ., ) were probably the main causes of the nondetection of this compound in plasma after oral and intra‐nasal administration, as observed in our previous work (Esposito et al ., ). In fact, desmopressin was only detectable in plasma after intravenous administration.…”
Section: Resultsmentioning
confidence: 97%
“…Finally, novel, previously unknown macromolecules (i.e., TB500 17-23 fragment), with no current approval for human therapeutic use (i.e., agents under preclinical or clinical development, designer drugs, or compounds approved only for veterinary use), but illegally marketed (e.g., via Internet websites) [5] are included in section S0 ''Non-approved substances''. Different analytical approaches have already been developed and published to detect these compounds in nutritional supplements [6][7][8][9][10] and in doping control samples (either blood [11][12][13][14][15][16][17][18] or urine [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]), employing immunological [26,[35][36][37], electrophoretic [16][17][18][19]27], or liquid chromatography-mass spectrometry techniques [6-15, 20-25, 28-34] or a combination of different analytical technologies. In general, the most effective analytical approach (combined sample pretreatment and the instrumental method) has to take into ...…”
Section: Introductionmentioning
confidence: 99%
“…Leu-Arg-Ile-Val-Gln-Cys-Arg-Ser-Val-Glu-Gly-Ser-Cys-Gly-Phe-OH Cys 7 and Cys14 1812.9ARA290 pGlu-Glu-Gln-Leu-Glu-Arg-Ala-Leu-Asn-Ser-Ser-…”
unclassified
“…This fragmentation was favorable because both compounds have a disulfide link between the two cysteine residues, and thus y-type fragmentation occurs, yielding y3 ions as the predominant products. 22 Effect of the mobile-phase solvent on sensitivity Figure 2 shows the effect of the aqueous solvent acid concentration of the mobile phase (using two different organic solvent mobile phases) on the assay sensitivity. We found that a low acid concentration in the aqueous mobile phase produced higher sensitivity for AVP, using methanol or acetonitrile as the organic mobile phase.…”
Section: Mass Spectra For Selecting the Ion Transition For Lc-ms/msmentioning
confidence: 99%